2020
DOI: 10.1088/0256-307x/37/4/040502
|View full text |Cite
|
Sign up to set email alerts
|

Dark Soliton of Polariton Condensates under Nonresonant PT -Symmetric Pumping*

Abstract: A quantum system in complex potentials obeying parity-time ( P T ) symmetry could exhibit all real spectra, starting out in non-Hermitian quantum mechanics. The key physics behind a P T … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 34 publications
0
8
0
1
Order By: Relevance
“…The time evolution of the parameters in Eq. ( 7) can be then obtained via the Euler-Lagrangian equations for the dissipative system [43][44][45][46][47]…”
Section: The Theoretical Model and Lagrangian Approachmentioning
confidence: 99%
“…The time evolution of the parameters in Eq. ( 7) can be then obtained via the Euler-Lagrangian equations for the dissipative system [43][44][45][46][47]…”
Section: The Theoretical Model and Lagrangian Approachmentioning
confidence: 99%
“…The key assumption underlying the ansatz ( 7 ) is that the functional forms of the soliton and the impurity-induced function are preserved in the presence of perturbation, whereas the corresponding parameters become slowly time-dependent. The time evolution of the parameters in Equation ( 7 ) can be obtained via the Euler-Lagrangian equations for the dissipative system [ 47 , 48 , 49 , 50 , 51 ] with and , and labels the real part of the expression. In Equation ( 8 ), the Lagrangian is referred to as the average Lagrangian of Equation ( 6 ) with , where the Lagrangian density is given by …”
Section: The Theoretical Model and Lagrangian Approachmentioning
confidence: 99%
“…They found that there existed multiple frequency windows where PT symmetry was broken and restored. The non-Hermitian Rabi model has drawn growing attention due to its especially rich phenomena which are absent in the static counterparts [37][38][39][40][41][42][43][44][45]47]. Lee et al found the PT symmetry breaking at the (2k−1)-photon resonance and derived the boundaries of the PT phase diagram by doing perturbation theory beyond rotating-wave approximation [37].…”
Section: Introductionmentioning
confidence: 99%